Airship robust path-tracking: A tutorial on airship modelling and gain-scheduling control design. (May 2016) - Moutinho, Alexandra; Azinheira, José Raul; de Paiva, Ely C.; Bueno, Samuel S.
Abstract: This paper provides a tutorial view on airship path-tracking under wind disturbances. It addresses the relevant aspects towards this objective, namely the airship modelling, the dynamics analysis over the flight envelope, and the step-by-step design of a gain-scheduling control. The required parts to build a proper airship simulator are given: airship dynamics and actuation, and wind disturbances. A path-tracking gain-scheduling controller is designed and its performance and robustness evaluated in the simulation environment described for a complete airship mission consisting of vertical takeoff and landing, cruise flight and ground-hover, under realistic wind disturbances. Throughout the paper, considerations are done regarding the airship behavior and limitations, as well as what can be accomplished and how. Abstract : Graphical abstract: Abstract : Highlights: A tutorial view on control design for airship robust path-tracking is presented. A thorough airship dynamics analysis over the flight envelope is provided. The gain-scheduling control design is detailed for straightforward application. Airship model and simulator include wind disturbances influence. The complete path-tracking mission chosen demonstrates robustness of solution.